ANALISIS IMPLEMENTASI PROGRAM KESEJAHTERAAN KARYAWAAN PADA PERUSAHAAN KG INDONESIA (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In the current era of globalization, employees are increasingly aware of their rights, including their entitlement to welfare programs. This growing awareness is reflected in the willingness of employees, particularly across generations, to express their aspirations in advocating for these rights. This study aims to examine the implementation of employee welfare programs at KG Indonesia, focusing on the types of programs offered, the challenges encountered, and the solutions undertaken. The research employs a qualitative method, utilizing interviews, observations, and documentation for data collection. The analysis involves permanent employees with varying lengths of service who have direct experience with the implementation of these programs. The findings indicate that the company has implemented various welfare initiatives, including health insurance, annual bonuses, training programs, and recreational activities. However, challenges persist, especially regarding the uneven dissemination of information and the lack of understanding of the program’s benefits. These insights are expected to contribute to the enhancement of welfare program implementation in the future.Di era globalisasi saat ini, kesadaran karyawan terhadap hak-hak mereka, termasuk program kesejahteraan, semakin meningkat. Hal ini terlihat dari keberanian karyawan dalam menyuarakan aspirasi, terutama antar generasi. Penelitian ini bertujuan untuk menggambarkan pelaksanaan program kesejahteraan karyawan di Perusahaan KG Indonesia, mulai dari jenis program, tantangan, hingga solusi yang dilakukan. Metode penelitian menggunakan pendekatan kualitatif dengan teknik wawancara, observasi, dan dokumentasi. Informan terdiri dari karyawan tetap dengan latar belakang masa kerja yang beragam. Hasilnya, perusahaan telah menyediakan program kesejahteraan seperti jaminan kesehatan, bonus, pelatihan, dan kegiatan rekreasi. Namun, kendala masih ditemui, terutama dalam hal distribusi informasi yang belum merata dan minimnya pemahaman terhadap manfaat program. Banyak karyawan, khususnya yang baru, mengetahui informasi hanya melalui obrolan informal. Temuan ini menjadi masukan untuk memperbaiki implementasi program di masa mendatang.